THE FRACTIONATION BETWEEN Y AND HO IN THE MARINE ENVIRONMENT - Nozaki Y.; Zhang J.; Amakawa H. (My University, 1997)
New measurements of Y and Ho in seawater, rivers and rain are presented. Based on the data and a two-box model calculation, we suggest that fractionation between Y and Ho takes place during their removal by particulate matter from the surface ocean to the deep sea. The fractionation factor, KD is calculated to be 0.50, implying that Ho is scavenged two times faster than Y. This presumably occurs due to differences between Y and Ho complexation behavior with respect to seawater inorganic ligands (mainly carbonate ions) and soft organic ligands (though unspecified) of the surface of particulate matter. Fractionation of Y and Ho during weathering and fluvial transport to the ocean appears to have minor influence on the relative abundance of Y and Ho in seawater.We also estimated the mean oceanic residence time to be 5100 years for Y and 2700 years for Ho. Y is less effectively scavenged from seawater than any of the trivalent rare earth elements and the Y/Ho ratio in seawater is higher than those in rain, rivers and estuarine waters.
Keywords: YTTRIUM; HOLMIUM; SEAWATER; CHEMICAL FRACTIONATION; RESIDENCE TIME